1982
DOI: 10.1002/jobm.19820220204
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characteristic of non‐streptomycin‐producing mutants of Streptomyces griseus. II. Lipids and fatty acid composition of vegetative mycelia

Abstract: Five non-streptomycin-producing non-aerial-mycelium-forming mutants (Str-Amy-) of Streptomyces griseus obtained either by spontaneous degenerat,ion or during continuous cultivation of the high-producing aerial-mycelium-forming parent strain HP (Str+Amy+) were checked with regard to t'he composit,ion of mycelial lipid material. All the Str-Amy-derivatives differed from their ancestor strain HP by an increased ratio of 13-methyltetradecanoic acid (aCl5:O) to isopalmitic acid (iC16 :0) during growth on a chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Although different culture conditions were used clones altered in differentiation as observed in investigations under similar conditions with S. hygroscopicus , ROTH et al 1982a, GRXFE et aZ. 1982a) and S. griseus (ROTH et al 1982b, GRXFE et al 1981, 1982b) did not appear. All colonies growing from mycelium withdrawn from the continuous cultures formed aerial mycelium and spores as well as the red pigment.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Although different culture conditions were used clones altered in differentiation as observed in investigations under similar conditions with S. hygroscopicus , ROTH et al 1982a, GRXFE et aZ. 1982a) and S. griseus (ROTH et al 1982b, GRXFE et al 1981, 1982b) did not appear. All colonies growing from mycelium withdrawn from the continuous cultures formed aerial mycelium and spores as well as the red pigment.…”
Section: Resultssupporting
confidence: 86%
“…Beside the neomycin resistance we monitored the stability of S. liuidans 66-PM1 with respect to aerial mycelium and pigment formation in the course of the experiments. Although different culture conditions were used clones altered in differentiation as observed in investigations under similar conditions with S. hygroscopicus , ROTH et al 1982a, GRXFE et aZ. 1982a) and S. griseus (ROTH et al 1982b, GRXFE et al 1981, 1982b) did not appear.…”
Section: Resultsmentioning
confidence: 89%
“…In this context, it may be of some interest that actinomycetes form lipoamino acids, when essential phosphates are exhausted [26,27]. During bacterial life, phosphate deficiency may trigger sporulation [28], suggesting, formation of LS‐like surfactants could induce or, at least, support TGase cross‐linking in the cell wall of aerial mycelium.…”
Section: Resultsmentioning
confidence: 99%
“…When the autoregulator was present in cultures of Table 1 Mycelial fatty acids from surface cultures of S. griseus JA 5142 (P: parental strain), blocked mutant ZIMET 43682 (C: control) and ZIMET 43682 + autoregulator (F: factor added). Abbreviations: i14:1, 12-methyltridecanoic acid; 14:O. tetradecanoic acid; a15:0, 12-methyltetradecanoic acid; i16:0, isopalmitic acid; 16:0, palmitic acid; 16: 1, palmitoleic acid; a17 :0, 14-methylhexadecanoic acid; 18:0, stearic acid (GRAFE et al 1982b) suggesting that alterations of membrane structure and function may take place during the cell cycle of streptoniycetes. But from the differences found in cytochrome spectra and lipid coniposition of mutant ZIMET 43682 after addition of autoregulator it should not be concluded that this endogenous effector initially interferes with cellular systems accomplishing the synthesis of components of the cytoplasmic membrane.…”
Section: Resultsmentioning
confidence: 99%